2017
DOI: 10.1109/tsp.2017.2684743
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Nyquist Cyclostationary Detection for Cognitive Radio

Abstract: Abstract-Cognitive Radio requires efficient and reliable spectrum sensing of wideband signals. In order to cope with the sampling rate bottleneck, new sampling methods have been proposed that sample below the Nyquist rate. However, such techniques decrease the signal to noise ratio (SNR), deteriorating the performance of subsequent energy detection. Cyclostationary detection, which exploits the periodic property of communication signal statistics, absent in stationary noise, is a natural candidate for this set… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…It is also able to recover the power spectra of stationary signals, which makes the approach applicable even for non-sparse signals. It has been further proved that cyclic spectrum can be reconstructed from sub-Nyquist samples without sparsity constraint on the signals [39].…”
Section: Submentioning
confidence: 99%
“…It is also able to recover the power spectra of stationary signals, which makes the approach applicable even for non-sparse signals. It has been further proved that cyclic spectrum can be reconstructed from sub-Nyquist samples without sparsity constraint on the signals [39].…”
Section: Submentioning
confidence: 99%
“…The structure of R a x (f ), for a given a ∈]0, fs] andf ∈ [0, fs − a] was analyzed in [26]. It was found that the non zero entries of R a…”
Section: Iv-a Relation Between Samples and The Cyclic Spectrummentioning
confidence: 99%
“…It follows that R a x (f ) is 2K-sparse with additional structure. A detailed analysis can be found in [26].…”
Section: Iv-a Relation Between Samples and The Cyclic Spectrummentioning
confidence: 99%
See 2 more Smart Citations